Assessment of a tachinid fly and an egg parasitoid as biocontrol agents of Edessa meditabunda (Hemiptera: Pentatomidae) - Cingolani, María Fernanda (2024)
Phytophagous stink bugs are major pests of several crops. Among them, Edessa meditabunda (Hemiptera: Pentatomidae) has gained greater importance in the Neotropics in the last two decades. We aimed to evaluate the performance of two parasitoids of different guilds, as potential candidates for the biocontrol of E. meditabunda: the tachinid fly Neobrachelia edessae which exploits adults as hosts and the egg parasitoid Trissolcus urichi (Hymenoptera: Platygastroidea). In the first case, biological information of N. edessae is practically lacking while T. urichi is an important parasitoid of various pentatomids but little is known about its ability to attack E. meditabunda eggs.